If “No” Say It, If “Yes” Do It! Assertiveness and Procrastination in Psychology Students - Prakoso, Yogi Adi (Faculty of Psychology, Universitas Surabaya, 2013)
Procrastination is a deliberate delay, and repetitive, with no rational reason. The delay was done despite knowing the negative impact of the result of postponement. A study concerning procrastination found 90% of students procrastinate (Klassen, Krawchuk, & Rajani, 2008). Assertiveness is one of some aspects affecting procrastination. The aim of this study was to correlate assertiveness and procrastination in students who are participating in the Test Construction (Penyusunan Alat Ukur=PAU) (N=131), due to the high frequency of pro- crastination occuring in the academic sphere (Liu, 2010). The author also assesses two variables with Temporal Motivation Theory (Steel, 2007) as the conceptual frame. Data was analyzed using SPSS 13.0 for Windows, assertiveness scale using Rathus Asertiveness Schedule (Rathus, 1973), and Pure Procrastination Scale. A correlation of - .372 was found. The causes are further discussed. Prokrastinasi merupakan penundaan yang dilakukan secara sengaja, dan berulang, dengan alasan yang tidak rasional. Hal ini dilakukan walaupun mengetahui adanya dampak negatif atas akibat penunda-nundaannya. Studi tentang prokrastinasi mendapati 90% mahasiswa berprokrastinasi (Klassen, Krawchuk, & Rajani, 2008). Salah satu aspek yang memengaruhi prokrastinasi adalah asertivitas. Tujuan penelitian adalah mengorelasikan asertivitas dan prokrastinasi pada mahasiswa yang sedang mengambil matakuliah Penyusunan Alat Ukur (PAU) (N= 131), mengingat seringnya prokrastinasi yang terjadi di lingkup akademik (Liu, 2010). Peneliti juga mengaji kaitan dua variabel menggunakan Temporal Motivation Theory (Steel, 2007) sebagai kerangka konseptual. Data kemudian dianalisis dengan program SPSS 13.0 for Windows. Skala asertivitas menggunakan Rathus Asertiveness Schedule, dan Pure Procrastination Scale. Studi ini mendapatkan hasil korelasi sebesar - .372. Sebab-sebabnya didiskusikan lebih lanjut.